Stock assessment of Metapenaeus monoceros (Fabricius) from Cochin waters, Kerala - Nandakumar, G; Srinath, M (Indian Journal of Fisheries, 2011)
Based on the catch and effort, and length distribution data of Metapenaeusmonoceros landed by shrimp trawlers at Cochin Fisheries Harbour during1991 - 93, an attempt has been made to assess the stock of this species in theCochin waters. The average annual instantaneous rate of total mortality wasestimated 7.06 and 7.75 for females and males respectively. The estimated valueof annual natural mortality (M) was 2.35 and it was assumed to be the same forboth sexes. The estimate of fishing mortality rate (F) was 4.71 for females and5.40 for males of M. monoceros. The average rate of exploitation (E) was 0.70and 0.67 respectively for males and females. The average standing stock size ofM. monoceros for the period under study was 10.55 t for males and 28.65 t forfemales. The Thomson and Bell and the Beverton and Holt yield per recruitroutines in the LFSA are used to explain the present status of fishery which showsthat there is no adverse effect of fishing on the exploited stock of M. monocerosfrom the southwest coast off Cochin.